Evaluating the Effectiveness of Clustering-Based K-Anonymity and KNN Cluster for Privacy Preservation - Kanade, Dhananjay M.; Sane, Shirish S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Due to the increasing number of data-driven innovations, privacy preservation has emerged as a paramount concern in the domain of data anonymity. Several techniques have been proposed to address this issue, and this paper aims to evaluate the three most popular ones. The study will look into clustering-based k-anonymity with KNN Cluster and K-Member with K=5 and 10. The importance of preserving personal information has become more apparent in the age of big data. Due to the increasing processing capabilities and the amount of data collected, the risk of unauthorized access and breaches has increased. This has prompted the need for effective data anonymization strategies. One of the most common methods of protecting personal information is by grouping similar people into clusters. This method ensures that each member of the group is indistinguishable from the others within the cluster. Another method is the KNN Cluster algorithm, which takes into account the proximity of the individuals to the feature. Finally, the K-Member algorithm is designed to identify the most representative of a given dataset. The paper aims to analyze and compare the three most popular methods for protecting personal information. We performed experiments with varying values of k, such as k=5 and k=10, to evaluate their privacy preservation effectiveness. The study is conducted on a scale of data utility, computational efficiency, and information loss. The results of the study will be analyzed and compared to provide a comprehensive understanding of the various limitations and strengths of each approach. This research will also help policymakers, data scientists, and data custodians make informed decisions when it comes to implementing anonymization strategies. The paper provides an in-depth evaluation of the clustering-based KNN Cluster, K-Member, and K-Anonymity techniques, focusing on their privacy effectiveness when protecting varying values of k. Its findings will help advance the field of privacy-enhancing mechanisms in the context of data-driven applications, and it will facilitate the creation of more robust and efficient methods